PHP 5 for dummies - Valade, Janet (For dummies, 2004)
Uses a friendly, easy-to-understand style to show Web designers how to use the latest major release of PHP, the most popular open source Web scripting language. PHP is easy to learn, database-friendly, and especially well suited for Web development because it can be embedded with HTML. .